Coronary Microvascular Dysfunction - Shigeo Godo; Akira Suda; Jun Takahashi; Satoshi Yasuda; Hiroaki Shimokawa (2021)
Over the past couple of decades, accumulating evidence has shown that structural and functional abnormalities of coronary microvasculature are highly prevalent, associated with adverse clinical outcomes in patients with various cardiovascular diseases. The term coronary microvascular dysfunction (CMD) has been coined to refer to this clinical condition and is increasingly recognized as an important clinical entity in many clinical settings. The potential mechanisms of CMD appear to be heterogenous, including enhanced coronary vasoconstrictive reactivity at microvascular level, impaired endothelium-dependent and independent coronary vasodilator capacities, and increased coronary microvascular resistance secondary to structural factors. Recent experimental and clinical studies have highlighted emerging modulators of vascular functions, vital insight into the pathogenesis of cardiovascular diseases associated with CMD, and potential therapeutic interventions to CMD with major clinical implications. In this article, we will briefly review the current progress on pathophysiology, molecular mechanisms, and clinical management of CMD from bench to bedside.